Salivary testosterone and cortisol changes during a game in professional male basketball players - Cabarkapa, D.; Eserhaut, D. A.; Cabarkapa, D. V.; Philipp, N. M.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2023)
The purpose of this study was to examine acute changes in salivary testosterone (T), cortisol (C), and testosterone-to-cortisol ratio (T/C) during a simulated 5-on-5 basketball game. Seven professional male basketball players volunteered to participate in this study. Repeated-measures analysis design was used to examine changes in hormonal concentrations across 8 testing time points: immediately upon arrival to the gymnasium-baseline (BS); post-warm-up (PW); post-first (P1Q), second (P2Q), third (P3Q), and fourth quarter (P4Q); and 30 (P30) and 60 minutes (P60) postgame. The findings of this study indicate that a simulated 5-on-5 basketball game provoked significant changes in salivary T, C, and T/C. When compared to the BS levels (x¯ ± SD [nmol·L-1]; 6.72 ± 2.53), salivary C concentration experienced a notable increase P3Q (16.20 ± 7.70) and remained elevated throughout the rest of the sampling periods, with values failing to return to BS levels P60 (11.88 ± 5.58). Conversely, a significant increase in salivary T occurred P1Q (0.76 ± 0.21) when compared to the BS levels (0.58 ± 0.12) and remained elevated up to P30 (0.75 ± 0.20), with values returning to BS levels P60 (0.63 ± 0.14). In addition, despite no significant intragame alterations, T/C exhibited a notable decrease P30 (0.06 ± 0.02) and P60 (0.07 ± 0.04), when compared to BS values (0.10 ± 0.04). Overall, these findings provide additional insight into the physiological stress that basketball players are exposed to during 5-on-5 competitive play and can be used to appropriately adjust and monitor training loads to optimize recovery and on-court basketball performance.